Existence of Positive Solutions for Neumann Boundary Value Problem with a Variable Coefficient - Dongming Yan; Qiang Zhang; Zhigang Pan (International Journal of Differential Equations)
We consider the existence of positive solutions for the Neumann boundary value problem x′′(t)+m2(t)x(t)=f(t,x(t))+e(t),t∈(0,    1),x′(0)=0,x′(1)=0, where m∈C([0,1],(0,+∞)),e∈C[0,1], and f:[0,1]×(0,+∞)→[0,+∞) is continuous. The theorem obtained is very general and complements previous known results.